THE IMPORTANCE OF SERVICE PLACEMENT AND CHANNELLINGTO PREPARE HUMAN RESOURCES FOR STUDENTS TO MEET THE CAREERS OF THE FUTURE - Dewi Mariana (JETL (Journal of Education, Teaching and Learning), 2016)
Placement and distribution Service aimed at helping put and passing students in accordance with the potential, interests, and talents. Placement and distribution services, namely continuous process to facilitate learners achieve success the process and results of the study as well as optimal development in order to achieve the goals of national education. Guidance and counselling Services in the form of peminatan provide ample opportunity for learners to channel and put yourself on the path to a more appropriate in the framework of the completion of the studies are focused, successful, educated and clear in next. The purpose of the service placement and channelling instill interest subjects, confirming the interest of subjects, as well as select and establish an interest group of subjects, the cross-subjects and study subjects who followed in the education unit, which was being pursued, career choice and/or advanced course options up to the College